Pengembangan E-Modul Menggunakan Flipbook Berbasis Creative Problem Solving Untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa - Dian Armanto; Vian Anotona Giawa (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
Mathematics is a universal science that underlies the development of modern technology, plays an important role in various scientific disciplines, and human thinking abilities. The view that mathematics is a science that trains thinking. The Creative Problem Solving learning model is a learning model that focuses on teaching and Problem Solving skills. Digital teaching materials are use digital devices, such as computers, smartphones. The aim of this research is to see the validity, practicality and effectiveness of the e-module being developed. This teaching material development model uses the ADDIE model. This research was carried out at SMP Negeri 21 Medan which is located on Jl. Rampe Raya flower. The time for the panel research is the even semester of the 2023/2024 academic year. The subjects of this research were class VII students at SMP Negeri 21 Medan. Meanwhile, the object of this research is learning media in the form of e-modules using flipbooks based on Creative Problem Solving. The e-module was declared very valid with a score of 3.56 and was categorized as very feasible. The e-module was declared practical with a percentage of 92.67% and was categorized as very practical. The e-module was declared effective by achieving Problem Solving indicators in indicators 1, 2, 3 and 4 with 65% of students completing the learning. The achievement of classical student indicators has met 65% of students who took part in learning with a score of 75. And there was a significant increase in indicators 1, 2, 3, and 4.